Facile and efficient conjugate additions of b-dicarbonyl compounds and nitroalkanes to 4-aryl-4-oxobut-2-enoates - XIN LV (Journal of the Serbian Chemical Society, 2011)
Facile and efficient conjugate additions of carbon nucleophiles, such as b-dicarbonyl compounds and nitroalkanes, to 4-aryl-4-oxobut-2-enoates have been achieved under simple base catalysis. A variety of multi-functional g-keto esters could be conveniently obtained in good to excellent yields with complete regioselectivity.